Choosing the Right Routes: Vocabulary Learning Strategies for Diverse EFL Learners - Sukserm, Patsawut (SOCIAL SCIENCES RESEARCH AND ACADEMIC JOURNAL, 2024)
The main aim of this article is to analyze different vocabulary learning strategies for EFL learners. This article categorizes these strategies into five key areas: Determination, Social, Memory, Cognitive and Metacognitive strategies. Each category is examined in detail, including a discussion of both the benefits and challenges associated with the strategies. The article highlights how these strategies can be adapted to different types of vocabulary, including general, academic and technical words, and how they can be tailored to the individual needs of learners. The significance of this article lies in its potential to inform educators about effective vocabulary teaching practices and to contribute to research in the field of vocabulary acquisition.